Challenges of using a Fitbit smart wearable among people with dementia. (28th February 2023) - O'Sullivan, Grace; Whelan, Barbara; Gallagher, Niamh; Doyle, Priscilla; Smyth, Siobhán; Murphy, Kathleen; Dröes, Rose‐Marie; Devane, Declan; Casey, Dympna
Abstract: Objectives: Limited research on using smart wearables such as Fitbit devices among people with dementia has shown favourable outcomes. The aim of this study was to explore the acceptability and feasibility of using a Fitbit Charge 3 among people with dementia, living in the community, who took part in the physical exercise component of the Comprehensive REsilience‐building psychoSocial intervenTion pilot study. Methods: A mixed methods study was conducted; Quantitative data relating to wear rates for the Fitbit were recorded and qualitative data were collected by group and individual interviews with the people with dementia and their caregiver about their experience of wearing/using the Fitbit in the study. Results: Nine people with dementia and their caregiver completed the intervention. Only one participant wore the Fitbit consistently. Supporting set‐up and use of the devices was time consuming and caregiver involvement was essential for day‐to‐day support: none of the people with dementia owned a smartphone. Few of them engaged with the Fitbit features, primarily only using it to check the time and only a minority wanted to keep the device beyond the intervention. Discussion: When designing a study using smart wearables such as a Fitbit among people with dementia, consideration should be given to the following: the possible burden on caregivers supporting the use of the device; a lack of familiarity with this technology in the target population; dealing with missing data, and the involvement of the researcher in setting up and supporting use of the device. Key points: Understanding the feasibility and acceptability of using smart wearables among people with dementia is important so that use in this group can be optimised. Caregiver involvement in supporting the person with dementia throughout the process is essential and should be acknowledged when developing further research in this area. Organising, cleaning and analysing the synced data from the Fitbit can be onerous and time consuming and so automated data management software should be considered for use in future studies if the benefits outweigh the cost of the software.